Urothelial Carcinoma Recurrence in an Ileal Neobladder Nine Years after Primary Surgery with Muir-Torre Syndrome - Floryn Cherbanyk; Marc Prod’homme; Edgardo Pezzetta; Bernard Chevaux; Anass Anaye; Jean-Joseph Boillat (Case Reports in Urology)
We report a patient who presented with a urothelial carcinoma recurrence developed nine years after radical cystoprostatectomy, related to Muir-Torre syndrome.